Urinary Cell-Free miR-99a-5p as a Potential Biomarker for Estrus Detection in Buffalo - Hebbar, Aparna; Chandel, Rajeev; Rani, Payal; Onteru, Suneel Kumar; Singh, Dheer (Frontiers in Veterinary Science, 2021)
Accurate estrus detection method is the need of the hour to improve reproductive efficiency of buffaloes in dairy industry, as the currently available estrus detection methods/tools lack high sensitivity and specificity. Recently, circulating miRNAs have been shown as noninvasive biomarkers by various studies. Hence, in order to evaluate their potential as estrus biomarkers, the objective of this study was to identify and compare the levels of ten hormone responsive miRNAs in the urine collected at proestrus (PE), estrus (E) and diestrus (DE) phases of buffaloes (n=3) pertaining to a discovery sample. Among ten urinary miRNAs, the levels of bta-mir-99a-5p (E/PE 0.5-fold,P<0.05; DE/PE 1.9-fold), bta-miR-125b (E/PE 0.5-fold; DE/PE 0.7-fold), bta-mir-145 (E/PE 1.5-fold; DE/PE 0.7-fold), bta-mir-210 (E/PE 1.2-fold, DE/PE 0.7-fold), mir-21 (E/PE 1.5-fold, DE/PE 2-fold) and bta-mir-191 (E/PE 1.3-fold; DE/PE 0.8-fold) were found to be altered during different phases of buffalo estrous cycle. In contrast, bta-mir-126-3p, bta-let-7f, bta-mir-16b and bta-mir-378 were undetected in buffalo urine. Furthermore, a validation study in an independent group of 25 buffalo heifers showed the increased levels of urinary bta-mir-99a-5p during the diestrus (3.92-fold; P<0.0001) phase as compared to the estrus phase. Receiver Operating Characteristic curve analyses also revealed the ability of urinary miR-99a-5p in distinguishing the estrus from the diestrus phase (Area under curve of 0.6464; P <0.08). In silico analysis further showed an enrichment of miR-99a-5p putative targets in various ovarian signaling pathways, including androgen/estrogen/progesterone biosynthesis and apoptosis signaling, implicating the role of miR-99a-5p in ovarian physiology. In conclusion, significantly lower levels of bta-mir-99a-5p at the estrus phase than the diestrus phase in buffalo urine indicate its biomarker potential, which needs to be further explored in a large cohort in the future studies.